Encapsulated MAPbBr3 in nickel oxide nanotubes and their electroluminescence. Issue 17 (13th April 2022) - Gonzalez-Rodriguez, Roberto; Hathaway, Evan; Lin, Yuankun; Coffer, Jeffery L.; Cui, Jingbiao
Abstract : Perovskite nanowires encapsulated inside nickel oxide nanotubes were studied. This unique structure showed a stable and efficient electroluminescence for potential LED applications. Abstract : Metal halide perovskites have emerged as the next generation of light emitting semiconducting materials due to their excellent properties such as tunable bandgaps, high photoluminescence quantum yield, and high color purity. Nickel oxide is a hole transport material that has been used in planar light emitting diodes (LEDs). In this paper, we develop a novel method for the large scale fabrication of metal halide perovskite nanowire arrays encapsulated inside nickel oxide nanotubes. We study the structural and spectral properties of these infiltrated perovskites nanowires and, to the best of our knowledge, for the first time report on a working LED device consisting of perovskites encapsulated inside nickel oxide nanotubes. Finally, we study the photoluminescence and electroluminescence of an LED with MAPbBr3 inside nickel oxide nanotubes and obtain an outstanding current efficiency of 5.99 Cd A −1 and external quantum efficiency of 3.9% for the LED device.